Liquid flow distribution in trickle bed reactors containing trilobed extrusions packed using different techniques - Aashna Suneja; Shantanu Roy (Results in Engineering, 2023)
The performance of the Trickle Bed Reactor (TBR) critically depends on the gas-liquid flow distribution in the reactor, which in turn depends on the catalyst shape, size, and structure. Extensive research has been carried out with spherical particles (catalyst),whereas industrially more complex-shaped particles (Cylindrical, Trilobe, and Quadrilobe) are used. Little work has been reported for the liquid distribution in packed beds employing these shapes.In this work, the liquid distribution was investigated in a cylindrical column of internal diameter 100 mm, containing particles of diameter 1.3 mm trilobed extrusions and length 1.8–8.8 mm. The influence of different loading methods - Central single source, solid cone, and hollow cone, gas and liquid flow rates, variation along the height of the column were studied. Air-water system was used. Pressure drop was measured with the help of a manometer and Maldistribution index (Mf) was calculated based on the variation of quantity of water collected at column outlet.It was observed that the Mf decreased with the increase in both the gas and liquid flow rate which was due to better spreading of the fluids with the increasing gas and liquid flow rate. The decrease in the Mf with the increasing gas and liquid flow rate indicates better distribution as reported in the literature 0 (best distribution) and 1 (worst distribution). Further, it was also noted that the pressure drop increased with the increasing gas and liquid flow rate. The hollow cone packing method shows the better distribution confirmed from the bulk voidage, Mf profiles, pressure drop variation, and flow profiles. A correlation has been proposed for the two-phase pressure drop for three packing methods.